2021
DOI: 10.1111/jph.12981
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence and characterization of virus species associated with black pepper (piper nigrum l.) virus diseases in Hainan province, China

Abstract: Black pepper (Piper nigrum L.) is one of the most ancient spice crops in the world. Hainan Province is the largest black pepper‐producing region in China. Viral disease is one of the main factors affecting black pepper. However, there are rarely studies on black pepper viral disease in China. We performed a survey in five major black pepper‐growing counties (Qionghai, Wenchang, Wanning, Haikou and Ding'an) of Hainan Province and collected 589 samples, with virus‐like symptoms from 2014 to 2019. Various viruses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 11 publications
0
8
0
Order By: Relevance
“…Recently, this disease has also been reported in China [4]. In Indonesia, this disease has been observed in black pepper plants since 1976.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…Recently, this disease has also been reported in China [4]. In Indonesia, this disease has been observed in black pepper plants since 1976.…”
Section: Introductionmentioning
confidence: 92%
“…In Indonesia, this disease has been observed in black pepper plants since 1976. A more recent report indicated that PYMoV is the main pathogen causing mottle disease in black pepper plantations in Sukabumi District of West Java, Indonesia [5] and Hainan, China [4].…”
Section: Introductionmentioning
confidence: 99%
“…The yellow mottle disease (also known as stunt disease) of black pepper ( Piper nigrum ) caused by the badnavirus, Piper yellow mottle virus (PYMoV) is reported in Brazil, China, India, Indonesia, Malaysia, Philippines, Sri Lanka, Thailand, and Vietnam [ 45 , 46 , 47 , 48 , 49 ]. The disease is characterized by chlorotic flecks, mild to severe mottles, and brittle, leathery, deformed, and reduced leaf size ( Figure 2 ).…”
Section: Emerging Disease Problems In Plantsmentioning
confidence: 99%
“…Lockhart et al [ 45 ] for the first time reported the association of a distinct badnavirus with yellow mottle disease affecting black pepper from Indonesia, Malaysia, Philippines, and Thailand and named it Piper yellow mottle virus (PYMoV) based on bacilliform virus particles, transmission by mealybug, its weak serological relationship with other badnaviruses, and its partial nucleotide sequence of the reverse transcriptase (RT)/RNase H region of the virus. Later association of PYMoV with black pepper was reported in Brazil [ 51 ], Sri Lanka [ 46 ], India [ 47 ], Vietnam, and China [ 48 ]. In addition to black pepper, PYMoV also infects other economically important Piper species such as P. betle (betelvine), P. longum (Indian long pepper), and many other wild Piper species [ 52 , 53 ].…”
Section: Emerging Disease Problems In Plantsmentioning
confidence: 99%
“…Mottle is a viral major disease in black pepper and has been reported in several producing countries, i.e. India, Thailand, Malaysia, Sri Lanka, Brazil, China and the Philippines, with disease incidence ranging from 10 to 45% (Lockhart et al, 1997;Hany et al, 2014;Che et al, 2021). In Indonesia, mottle disease has been observed in many black pepper plantations, among others in Purbalingga, Bangka and Yogyakarta Alif et al, 2018).…”
Section: Introductionmentioning
confidence: 99%